Instabilities and self-organization in materials - Ghoniem, N. M. (Nasr Mostafa); Walgraef, D. (Daniel) (Oxford : Oxford University Press, 2008)
Instabilities and self-organisation in materials are at the core of technological applications. In nano-technology, manufacturing of electronic and electromagnetic devices relies on the natural tendency of materials to undergo 'self-organisaton'. Fundamentals are covered in volume I and applications in volume II.
In slip case.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Materials science